School leadership and complexity theory - Morrison, Keith (Keith R. B.) (New York : Routledge/Falmer, 2002)
Applies the complexity theory to the topic of education, explaining how an understanding of the theory can lead to a better sense of school leadership.
Includes bibliographical references (p. [195]-212) and index.
Adult
Keywords: Complex organizations; Educational leadership; School management and organization; Educational leadership; Organizational sociology; Schools -- Administration